The Quality of Educational Service in Faculty of Education- Hajjah From the perspective of students of the scientific departments - Dawood Al-Hodabi; Huda Abdullah Gashwah (University of Science and Technology, Yemen, 2009)
The Quality of Educational Service in Faculty of Education- Hajjah From the perspective of students of the scientific departments abstract: The aim of this study is to explore the educational service quality level in Hajjah faculty of education - Hajjah, Amran University from the perspectives of the students in the scientific departments. The sample used in this study was all students of the scientific departments (Physics, Chemistry, and Biology) in the first and four levels. They were 300 students (male, female). A standerized tool was adopted for this study (Dawood AL-Hadabi, Mahmood Okasha, 2007). It was a questionnaire containing nine items(The scientific subject, academic staff, library, employers, admission, registration, student activities, the university image, employing, infrastructure). The results were analyzed by computer using the statistical programme (SРЅЅ). The results of this study:  1- The level of the educational service quality in Faculty of Education - Hajjah, Amran University is substandard. 2- There was no significant difference at (α= 0.05) for the level of educational service quality due to the variable of gender. 3- There were significant differences at (α= 0.05) for the level of educational service quality due to the variable of (Department, level).